Development of Hanjeli Tourism Village through The Digitalization of Website-Based Homestay Services and Tourism Packages - Siti Zakiah; Eva Mardiyana; Tito Pandu Raharjo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Desa Wisata Hanjeli has significant potential in terms of natural resources, cultural heritage, and local agricultural attractions. However, the management of tourism promotion and services has not yet been optimal, resulting in limited reach to a broader market. This community service activity aims to support the development of Desa Wisata Hanjeli through the application of appropriate technology in the form of website-based digitalization of homestay services and tourism packages. The implementation methods include partner needs analysis, web-based information system design, technology usage training for managers, and assistance in managing content and online reservation services. The developed website presents the village profile, homestay information, thematic tourism packages, and an easy-to-access booking facility for tourists. The results indicate that this digitalization improves the visibility of the tourism village, expands promotional reach, and provides convenience for tourists in accessing information and making reservations. In addition, the local community gains increased capacity in managing digital technology, enabling greater independence in marketing tourism products. Through this implementation, Desa Wisata Hanjeli is expected to enhance its competitiveness, strengthen the community-based economy, and promote sustainable tourism village development through the utilization of appropriate website-based technology.